The quantity and quality of different forage resources (fallow land, grassland and stubble) in the semi arid area of Sétif - Tedjari N.; Madani T.; Abbas K. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
This work aims at the knowledge of the pastoral resources productivity and quality used in the Sétifan High Plains. During one year (2003), monitoring the production and the nutritional value of natural pastures, fallow and stubble was conducted in seven farms. This study allowed us to move to the farm plot, specifying the feeding system characteristics; the floristic composition and the resources energetic value studied so far (fallow land, pastures and stubble). The results showed significant differences and varied according to the different seasons. For the grassland, the productivity is 11t/ha. It is of 3 to 4t/ha for stubble and mown fallow; while the production of grazed fallow is of 2t/ha.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)